Mandibular Bone Resorption Following Chin Augmentation: A Systematic Review - Yeung, Andy Wai Kan; Wong, Natalie Sui Miu (Frontiers in Surgery, 2022)
Background: Chin implants have a long history, and its usage may associate with mandibular bone resorption. Objectives: This report analyzed data on this topic from existing literature to evaluate the overall resorption rate and scientific impact in terms of citations. Method: PubMed, Web of Science, Scopus, and Google Scholar were searched to identify relevant publications. The search string was as follows: (chin) AND (augment* OR implant*) AND (resorb* OR resorp*) AND (bone OR osseous). A study was eligible if it recruited human subjects and reported resorption following any chin implantation based on radiographic examination. Results: Twenty-eight patient studies were identified. Publication year seemed to have no effect on the mean depth of bone resorption as well as its prevalence reported by the studies. Increased mean number of follow-up years seemed to have no effect on its prevalence, but associate with deeper bone resorption. The majority of the studies had < 5 years of follow-up and reported a mean of < 2 mm of bone resorption. The most cited study had 69 citations. Citations rarely came from radiology journals. A limitation was that unpublished data could not be analyzed. Conclusions: Mandibular bone resorption caused by chin implants of various materials is a common phenomenon. Its recognition and studies with a longer follow-up period should be further promoted.